Effectiveness of affirmation therapy on stress among nurses working in intensive care units at selected hospitals at Chennai: Pilot study - Ms. Thulasi L; Dr. S. Vasantha (The Bioscan, 2024)
The primary aim of the study was to assess stress among nurses working at selected hospital. Job related stress among nurses has a cost for individual in term of health, well being and for organization in term of absenteeism and turnover which affects quality of patient care. Objectives: To assess level of stress among nurses working in intensive care units, to assess and compare the pre and post assessment of clinical variables among nurses working in intensive care units with stress, to assess the effectiveness of affirmation therapy on stress among nurses working in intensive care units and to find out the association between stress and selected background of nurses. A study was conducted on 10 staff nurses working in intensive care units. Modified stress assessment scale was used and requires 15-30 min to solve for each questionnaire. There was no significant association found between occupational stress, and age, sex, education, year of experience. Nurses have to face stress which could have negative impact on organizational environment in the future. Out of all considered causes of stress, workload is the major factor responsible for frequent occurrence of stress among majority of nurses.